Post-traumatic high vaginal stricture and hematocolpos impersonating vaginal septum in adolescent girl: a case report - Patel, Smeet; Patel, Sanjay; Bhadana, Priyanka; Shetty, Ria (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Vaginal stenosis was once a well-known condition in various nations. Vaginal stenosis can be caused by a variety of factors and manifest in a variety of ways. Because its occurrence is based on misinformation and cultural beliefs, acquired gynaetresia continues to be a major public health concern in underdeveloped nations, despite the fact that it is preventable. Traditional treatment involves an abdomino-perineal approach that requires a laparotomy. We are presenting a rare instance of vaginal stenosis following perineal trauma in an adolescent girl, which resulted in hematocolpos, and also as a novel laparoscopic technique to the management of significant vaginal stenosis.